An unusual (4, 6)-coordinated copper(II) coordination polymer: High efficient degradation of organic dyes under visible light irradiation and electrochemical properties. (1st July 2018) - Zheng, Tian-Rui; Blatov, Vladislav A.; Qian, Lin-Lu; Tang, Ding-Yi; Zhang, Ya-Qian; Wang, Zhi-Xiang; Li, Bao-Long; Wu, Bing
Graphical abstract: An unusual 2-fold interpenetrating (4, 6)-coordinated 3D coordination polymer is a highly efficient and universal photocatalyst for the degradation of the organic dyes under visible light irradiation and its electrochemical performance was measured. Abstract: A copper(II) coordination polymer [Cu(itp)(ip)][Cu4 (OH)2 (itp)(ip)3 ]·4H2 O n (1 ) (itp = 1-imidazol-1-yl-3-(1, 2, 4-triazol-4-yl)propane, ip = isophthalate) was synthesized and characterized. 1 exhibits an intriguing 2-fold interpenetrating array of (4, 6)-coordinated 3D nets of the fsc topological type, which are based on the 4-coordinated single copper(II) and 6-coordinated tetranuclear hydroxy copper(II) [Cu4 (μ3 -OH)2 ] cluster. 1 is a highly efficient and universal photocatalyst for the degradation of the organic dyes methylene blue (MB), rhodamine B (RhB) and methyl orange (MO) under visible light irradiation. Electrochemical performance of 1 was also measured.